Impact Of Freight Transportation On Cd. Juárez Environment And Review Of Aerodynamic Drag Reduction Devices For Heavy Trucks - Tilvaldyev, Shehret (2021)
Nowadays studying the ways in which greenhouse gas emissions may be reduced from all sectors of human been activities, including the transportation sector, became extremely important. The purpose of this investigation is study environmental impact of freight transportation in cd. Juarez area and review of aerodynamic drag reduction devices for heavy trucks to better understand what technologies or practices can be applied to highway tractor and trailer combinations to reduce aerodynamic drag without negatively affecting the usefulness or profitability of the vehicles.